The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1021/acssuschemeng.7b02910
|View full text |Cite
|
Sign up to set email alerts
|

Production of High Levels of Chirally Pure d-2,3-Butanediol with a Newly Isolated Bacillus Strain

Abstract: 2,3-Butanediol (2,3-BD), especially when it exists in the chirally pure form, is a valuable chemical feedstock with numerous applications in various industries. However, in most cases, the 2,3-BD naturally produced by the microorganism is a mixture of two of the three isomers (d-2,3-BD, l-2,3-BD, and meso-2,3-BD), which has restricted applications and thus a much lower value than the chirally pure one. In this study, we report a new isolate Bacillus spp. FJ-4 strain, which can produce highly chirally pure d-2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…The previous study found that oxygen supply favors the high-level production of 2,3-BD [11]. Besides, the type of substrate and concentration, nitrogen source, and inorganic salts also significantly affect the 2,3-BD formation [11][12][13][14]. Recently, genetic engineering methods have been widely used to reduce the synthesis of byproducts and increase 2,3-BD production [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…The previous study found that oxygen supply favors the high-level production of 2,3-BD [11]. Besides, the type of substrate and concentration, nitrogen source, and inorganic salts also significantly affect the 2,3-BD formation [11][12][13][14]. Recently, genetic engineering methods have been widely used to reduce the synthesis of byproducts and increase 2,3-BD production [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…They were all confirmed as B. subtilis strains through the analysis of their 16S rDNA gene sequence (data not shown) . As a starting point, first, the six newly isolated strains along with the 168 strain (the type strain of B.…”
Section: Results and Discussionmentioning
confidence: 97%
“…B. subtilis N-3, N-5, N-6, A-1, FJ-1 and FJ-2 strains were newly isolated from fermented foods (Chinese natto and sufu from the local grocery store) as described previously . 2,3-BD fermentations were carried out using the 2,3-BD fermentation medium (containing 117.3 g/L sucrose; 15 g/L yeast extract; 3 g/L tryptone; 3 g/L NaCl; 3 g/L (NH 4 ) 2 SO 4 ; 0.6 g/L MgSO 4 ; 1 mM FeSO 4 ; 1 mM CaCl 2 ; 1 mM MnSO 4 and 1 mM ZnCl 2 ) in 250 mL shaking flasks at 37 °C and 150 rpm for 120 h. When sugar cane juice was used as the feedstock, two times diluted sugar cane juice (contains 91.7 g/L sucrose, 11.9 g/L glucose, 8.9 g/L fructose) was used to replace the sucrose in the 2,3-BD fermentation medium.…”
Section: Methodsmentioning
confidence: 99%
“…Microbial BDO production has been widely under investigation as a more sustainable process than chemical synthesis. However, the high cost of commercial sugars and downstream separation and purification (DSP) of BDO are serious drawbacks for industrial implementation. , The utilization of crude glycerol could reduce BDO production costs if high fermentation efficiency is achieved and synthetic fermentation media are used . Yang et al reported a high BDO concentration of 102.3 g/L under fed-batch mode using crude glycerol supplemented with molasses.…”
Section: Introductionmentioning
confidence: 99%